1989
DOI: 10.1080/07349348908960539
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Coal Model Compounds During Simulated Chemical Coal Cleaning with Molten Hydroxides

Abstract: Coal model compounds, such as dibenzothiophene, its analogs and the hydroxylated derivatives of these compounds. were treated with molten hydroxides to evaluate the importance of nucleophilicity for the different alkali-metal hydroxides. The soluble hydroxylated model compounds were decomposed and desulfurized by RbOH or CsOH at lower temperatures and in less time than when decomposed by KOH or NaOH, indicating that molten hydroxides have varying degrees of nucleophilicity, the progression of nucleophilicity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Although the alkali leaching either alone or with dissolved oxygen is very effective for pyritic sulfur removal, yet it can also remove the organic sulfur, in this work about 78% organic sulfur could be removed (at alkali concentration of 0.25 molarity, partial pressure of oxygen of 200 psi, reaction time of 4 hours, at temperature 120 o C, and with particle size of 40µm).. Ca Michael (Nowak et al 1989) worked on the mechanism of organic sulfur removal from coal by sodium hydroxide NaOH, he observed that alkali hydroxide containing large alkali metal cation are more effective in decomposition of thiophenes and furan of organic sulfur present in the coal. B.R Utz (Utz, Friedman, and Soboczenski 1986) found the chemistry of molten alkali hydroxide for organic species in the coal.…”
Section: Organic Sulfurmentioning
confidence: 85%
See 1 more Smart Citation
“…Although the alkali leaching either alone or with dissolved oxygen is very effective for pyritic sulfur removal, yet it can also remove the organic sulfur, in this work about 78% organic sulfur could be removed (at alkali concentration of 0.25 molarity, partial pressure of oxygen of 200 psi, reaction time of 4 hours, at temperature 120 o C, and with particle size of 40µm).. Ca Michael (Nowak et al 1989) worked on the mechanism of organic sulfur removal from coal by sodium hydroxide NaOH, he observed that alkali hydroxide containing large alkali metal cation are more effective in decomposition of thiophenes and furan of organic sulfur present in the coal. B.R Utz (Utz, Friedman, and Soboczenski 1986) found the chemistry of molten alkali hydroxide for organic species in the coal.…”
Section: Organic Sulfurmentioning
confidence: 85%
“…Michael has worked on the mechanism of organic sulfur removal from coal by sodium hydroxide NaOH, he observed that alkali metal cation are more effective to decompose the thiophenes and furan of organic sulfur present in the coal, hence the alkali hydroxide has ability to remove not only pyritic sulfur but also organic sulfur (Nowak et al 1989). Oxidative desulfurization is promising technology for removing sulfur from coal at lower temperature and in economical way (Saikia, Khound, and Baruah 2014).…”
Section: Introductionmentioning
confidence: 99%
“…He observed that the ne particle size requires less reaction time for the conversion of pyrite as compared to coarse particle size. The desulfurization of coal with oxidative method highly reduces its corrosive effects (Ahmad et al 2019) Organic sulfur Although the alkali leaching either alone or with dissolved oxygen is very effective for pyritic sulfur removal, yet it can also remove the organic sulfur, in this work about 78% organic sulfur could be removed (at alkali concentration of 0.25 molarity, partial pressure of oxygen of 200 psi, reaction time of 4 hours, at temperature 120 o C, and with particle size of 40µm).. Ca Michael (Nowak et al 1989) worked on the mechanism of organic sulfur removal from coal by sodium hydroxide NaOH, he observed that alkali hydroxide containing large alkali metal cation are more effective in decomposition of thiophenes and furan of organic sulfur present in the coal. B.R Utz (Utz, Friedman, and Soboczenski 1986) found the chemistry of molten alkali hydroxide for organic species in the coal.…”
Section: Introductionmentioning
confidence: 91%